A qualitative study on the perspective and teaching practice of novice lecturers in a paramedic course - Mahmud, Alias; Alwi, Nor Hayati; Sulaiman, Tajularipin (Medical Education Department, School of Medical Sciences, Universiti Sains Malaysia, 2014)
Objective: The study aimed to obtain the perspective and teaching practice of novice lecturers serving at the training institutions, Ministry of Health Malayisa (MOH). Method: A qualitative research was conducted on four novice lecturers at the Medical Assistant College, Seremban. Data were obtained from interview and observation on their teaching in the lecture rooms. The data analysis was performed by using Nvivio 9 software. Result: In the aspect of the teaching perspective, the finding showed that there were two main themes; teaching concept and the teaching method. As far as the teaching concept concerned, respondents perceived that lecturers were the source of knowledge and those who transferred the knowledge to the students. Meanwhile, the second perspective related to the teaching approach in which lecturers need to use their experiences, they need to be knowledgeable and creative in their teaching. The integration of the themes formed the main perspective, which was the lecturer-centered teaching. In turn, in the teaching practice, it was consistent with their perspective whereby the approach of teaching is lecturer-centered. Conclusion: This study showed that new lecturers would employ the lecturer-centered approach. Apart from that, they were also lacking of the skills in terms of class control and value inculcation. The deficiency in both these aspects needs to be overcome as it can affect the effectiveness of the teaching, also the quality of the graduates produced.